Managing oil price risk in developing countries - Devlin, Julia (2004)
Presents a simple framework for understanding the impact of oil dependence on growth and surveys countries' use of stabilization and savings funds. Discusses an optimal savings and investment strategy for oil-exporting countries and the rationale for implementing savings and stabilization funds. Surveys country esperiences with stabilization and savings funds. Explores the potential benefits of using financial instruments to manage oil price risk. Examines the reasons for so few developing economies using financial instruments to manage price risks. Looks at some problems and mechanisms to mitigate the shortcomings of this approach. Presents some policy implications.